Working point of the EFG process. Issue 6 (5th March 2015) - Carroz, L.; Duffar, T.
<x xml:space="preserve">Abstract</x> This paper is an investigation on the EFG process working point. The objective is to find the relationship between the heating power and pulling rate for a given rod diameter. A simple and handy algebraic model is established taking into account heat balance at the interface, head losses in the melt and meniscus surface energy. From a given die and capillary channel geometry, links between growth parameters and crystal dimension are highlighted.